Does DCD Donor Time‐to‐Death Affect Recipient Outcomes? Implications of Time‐to‐Death at a High‐Volume Center in the United States. Issue 1 (25th August 2016) - Scalea, J. R.; Redfield, R. R.; Arpali, E.; Leverson, G. E.; Bennett, R. J.; Anderson, M. E.; Kaufman, D. B.; Fernandez, L. A.; D'Alessandro, A. M.; Foley, D. P.; Mezrich, J. D.
Abstract : For donation after circulatory death (DCD), many centers allow 1 h after treatment withdrawal to donor death for kidneys. Our center has consistently allowed 2 h. We hypothesized that waiting longer would be associated with worse outcome. A single‐center, retrospective analysis of DCD kidneys transplanted between 2008 and 2013 as well as a nationwide survey of organ procurement organization DCD practices were conducted. We identified 296 DCD kidneys, of which 247 (83.4%) were transplanted and 49 (16.6%) were discarded. Of the 247 recipients, 225 (group 1; 91.1%) received kidneys with a time to death (TTD) of 0–1 h; 22 (group 2; 8.9%) received grafts with a TTD of 1–2 h. Five‐year patient survival was 88.8% for group 1, and 83.9% for group 2 (p = 0.667); Graft survival was also similar, with 5‐year survival of 74.1% for group 1, and 83.9% for group 2 (p = 0.507). The delayed graft function rate was the same in both groups (50.2% vs. 50.0%, p = 0.984). TTD was not predictive of graft failure. Nationally, the average maximum wait‐time for DCD kidneys was 77.2 min. By waiting 2 h for DCD kidneys, we performed 9.8% more transplants without worse outcomes. Nationally, this practice would allow for hundreds of additional kidney transplants, annually. Abstract : Hundreds more kidney transplants could be performed in the United States each year if centers were willing to wait up to 2 hours for kidneys procured after circulatory death, with no decrease in outcome.